The Influence of Servant Leadership Style and Digital Organizational Culture on Strengthening Work Ethic and Employee Performance at RSAR Cileungsi - Albert Yansen; Dewa Kadeq Wista; Chairul Hakim (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
Healthcare services demand high levels of accuracy, responsiveness, and collaboration because they directly relate to patient safety and public trust. In Indonesia, hospitals are encouraged to strengthen governance, service quality, and the use of health information technology, making leadership, digital organizational culture, and work ethic crucial performance factors. This study aims to analyze the influence of servant leadership and digital organizational culture on strengthening work ethic and employee performance at Dr. Abdul Radjak Hospital (RSAR) Cileungsi. The background of the study is based on frequent leadership changes (5 times in the 2020-2025 period), low implementation of digital culture, and declining work ethic and high employee turnover. The research method used a quantitative approach with a random survey technique through the distribution of questionnaires with a Likert scale to 115 respondents from a population of 160 permanent employees of RSAR Cileungsi who have worked for more than 10 years. Data analysis used SEM PLS version 4 (Structural Equation Modeling with Partial Least Squares). The results showed that servant leadership had a significant positive effect on digital organizational culture (69.5%), while its effect on work ethic and employee performance was insignificant. Work ethic was shown to have a significant positive effect on employee performance (78.7%). Together, servant leadership and digital organizational culture had a significant positive effect on employee performance (47.3%).